Rocks in the Bag: Mourning and Stress in Young Unaccompanied Migrants - Palacín Bartroli, Càndid; Herrera-Gutierrez, Maria-Rosa; Montagud Mayor, Xavier; Velasco Vázquez, Miren Koldobike (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2023)
It is clear that the migration process produces consequences. For adolescents and young people unaccompanied by a family referent, the effects of this transit on their mental health are often associated with anxiety and depression, deepening their vulnerability. This paper addresses the feelings of loss, grief and stress experienced by these young people, but also the elaboration of the relationship as a tool for socio-educational intervention. A qualitative methodology was used to recover the voice of the protagonists: young migrants and professionals in the sector. The results highlight the incidence of some relevant stressors such as the journey or the absence of documents, among others. It also highlights the importance of mourning, as an integrating element of what has been lost, the present and the gestation of expectations, as well as the estimable effect of the link as a professional tool for social intervention with adolescents and young people.
Keywords: UMM; mourning; bonding; stress